Professional Hockey and Urban Development: A Historical Case Study of the Vancouver Arena, 1911–1914 - Wong, John (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2009)
AbstractThis paper investigates the Vancouver Arena, also known as the Denman Street Arena, and its impact in the immediate six city blocks along Georgia street between Bidwell and Chilco streets. An enterprise of the Patrick family, the Vancouver Arena was built in 1911 to house the Vancouver Professional Hockey Club in the new Pacific Coast Hockey Association, also a Patrick family undertaking. Prior to the Second World War, sport entrepreneurs generally subscribed to the principle of free enterprise, which eschewed government interference. Unlike professional team owners of today, they viewed government financial aid as corporate welfare, an idea antithetical to the capitalistic tendencies of business owners at the time. These early sport promoters usually raised capital through means other than government largess. Municipalities, on the other hand, did not consciously include sport facilities as part of their urban planning. Unlike in stadium and arena projects today, there were no efforts made by promoters to link the construction of a sport facility with the economic health of the city. The case of the Vancouver Arena demonstrates that a sport facility had minimal impact on its immediate vicinity, but the larger economic climate of the city and region had a more significant influence.